Peningkatan Kinerja SDM Melalui Pengelolaan dan Kualitas SDM Serta Motivasi SDM sebagai Variabel Intervening - Anggreani, Prita; Zamrudi, Muhammad Faisal Yul (Innovative: Journal Of Social Science Research, 2025)
This research aims to examine HR Performance Improvement through HR Management and Quality and HR Motivation as Intervening Variables. The research method used is quantitative research, because the data processed is numerical. Testing in this research was carried out using regression analysis and t test to test the hypothesized effect. The data analysis technique in this research uses Statistical Product and Service Solutions (SPSS 26). Apart from that, to test the influence of intervening variables using the Sobel test. The results of this research indicate that management has a significant influence on HR motivation. HR quality does not have a significant influence on HR motivation. Management does not have a significant influence on HR performance. HR quality has a significant influence on HR performance. HR motivation has a significant influence on HR performance. HR motivation is able to mediate the influence of management on HR performance. HR motivation is unable to mediate the influence of HR quality on HR performance.